New Bradoriid Arthropods from the Early Cambrian Balang Formation of Eastern Guizhou, South China - Peng Jin; Feng Hongzhen; Fu Xiaoping; Zhao Yuanlong; Yao Lu (WILEY-BLACKWELL, 2010)
The Early Cambrian Balang Formation is comprised of mudrock and shale, which was deposited in a shelf environment in the eastern part of Guizhou, south China. The Balang Fauna, which consists of seven phyla, occurs in the middle and upper parts of the Balang Formation. Arthropods are important constituents of the Balang Fauna and include a great number of trilobites, large bivalved arthropods, and newly-discovered well-preserved bradoriid fossils. The bradoriids present include three genera and four species: Comptaluta inflate (Cheng, 1974) emend Hou et al., 2002; Comptaluta kailiensis sp. nov, and Alutella elongeta sp. nov, Aluta sp. This faunal assemblage in the Balang Formation is distinguished from the Tsunyiella Chang, 1964, Songlinella Yin, 1978 and Kunmingella Hou, 1956 assemblage which occurs in the Niutitang and Mingxinsi formations of the Yangtze Platform in middle region of Guizhou and which is earlier than the Balang Formation in age. However, this assemblage resembles the Comptaluta Opik, 1968 assemblage from the Early Cambrian Heilinpu Formation in Wuding County, Yuanan Province and from the Ordian Stage of the Cambrian of Australia. The great abundance of Comptaluta Opik, 1968 and overall taxonomic diversity of the Comptaluta Opik, 1968 assemblage set it distinctly apart from the Alutella Kobayashi et Kato, 1951 and Aluta Hou, 1956 assemblages of the Balang Formation. Alutella Kobayashi et Kato, 1951 and Aluta Hou, 1956 also occur in the Early Cambrian Niutitang Formation of the Yangtze Platform of Guizhou. Individual Bradoriids from the Balang Formation are characterized by large size (> 3 mm). The discovery of new Bradoriid assemblages not only expands the group's geographical range and assemblage affinities, but also indicates that Bradoriids migrated eastward from shallow-water to deeper-water environments during the Early Cambrian, indicating that they were capable of life in deeper-water, and adaptation to a new ecological setting.